Cultural economics - Li, Yining (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Culture is a priceless inheritance and source of wellbeing that is of immense value to humankind. Cultural economics sets out to examine the nature and social benefits of cultural products and phenomena as they exist in the market. This volume is the masterpiece of Li Yining, one of the best-known Chinese economists, active in devoting his attention to the role of culture in the economy since the 1950s. Considering the importance of culture in the development of socialism with Chinese characteristics, the author combines cultural history, economic history and the history of economic thought to produce unique perspectives. This book not only introduces the central concepts of cultural economics and the culture industry, but proposes several groundbreaking views that greatly influenced the culture policies of China, including cultural adjustment, cultural confidence and cultural checks and balances. Researchers and students of economics, cultural studies, and Chinese politics, as well as policy makers, will benefit from this volume"--
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Culture -- Economic aspects -- China; Economics -- China -- Sociological aspects; BUSINESS & ECONOMICS / Development / Economic Development; BUSINESS & ECONOMICS / Economic History